Sammlung Ackermans - Blazwick, Iwona; Curiger, Bice; Heynen, Julian; Liebermann, Valeria; Reust, Hans Rudolf; Schmidt-Wulffen, Stephan; Zweite, Armin; Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
Boltanski, Christian ; Brandl, Herbert ; Cragg, Tony (Anthony) ; Deacon, Richard ; Demand, Thomas ; Devlin, Lucinda ; Fischli & Weiss ; Fritsch, Katharina ; Herold, Georg ; Honert, Martin ; Kabakov, Ilya ; Kim, Soo-Ja ; Kounellis, Jannis ; Merz, Mario ; Metzel, Olaf ; Mucha, Reinhard ; Mueck, Ron ; Muñoz, Juan ; Neshat, Shirin ; Oursler, Tony ; Pfeiffer, Paul ; Pistoletto, Michelangelo ; Rhoades, Jason ; Ruff, Thomas ; Schnabel, Julian ; Schütte, Thomas ; Stadtbäumer, Pia ; Viola, Bill ; Wall, Jeff ; Warhol, Andy ; West, Franz ; Whiteread, Rachel ; Woodrow, Bill
Duits
Engels
Sammlung Ackermans, K21 Kunstsammlung Nordrhein-Westfalen Düsseldorf, K21 Kunstsammlung Nordrhein-Westfalen Düsseldorf
boek